Influenza A Viruses Detected in Swine in Southern Germany after the H1N1 Pandemic in 2009. (23rd June 2016) - Pippig, J.; Ritzmann, M.; Büttner, M.; Neubauer‐Juric, A.
Summary: Infections with influenza A viruses (IAV) are highly prevalent in swine populations, and stable cocirculation of at least three lineages has been well documented in European swine – till 2009. However, since the emergence of the human pandemic pdmH1N1 virus in 2009, which has been (re)introduced into individual swine herds worldwide, the situation has been changing. These variations in the respective IAV pools within pig populations are of major interest, and the zoonotic potential of putative emerging viruses needs to be evaluated. As data on recent IAV in swine from southern Germany were relatively sparse, the purpose of this study was to determine the major IAV subtypes actually present in this region. To this aim, from 2010 to 2013, 1417 nasal swabs or lung tissue samples from pigs with respiratory disease were screened for IAV genomes. Overall, in 130 holdings IAV genomes were detected by real‐time RT‐PCR targeting the matrix protein gene. For further analyses, several PCR protocols were adapted to quickly subtype between H1, pdmH1, H3, N1 and N2 sequences. Taken together, cocirculation of the three stable European lineages of IAV was confirmed for Bavaria. H1N1 sequences were identified in 59, whereas H1N2 genomes were only diagnosed in 14, and H3N2 in 9 of the holdings analysed. However, pdmH1 in combination with N1 was detected in 2010, 2012 and 2013 confirming a presence, albeit in low prevalence, likewise pdmH1N2 reassortant viruses. Interestingly, individual cases of coinfections with more than one subtype were diagnosed. Partial genome sequences were determined and phylogenetic analyses performed. Clearly other than in the human population classically circulating IAV have not been displaced by pdmH1N1 in Bavarian swine. However, some interesting viruses were detected. Further surveillance of these viruses in the Bavarian pig population will be of major importance, to monitor future developments.